Conceptual Overview of Prevalence of Prediabetes - Monika; Arora, Pragi; Kumar, Varun; Popli, Pankaj (Current Diabetes Reviews, 2025)
Prediabetes increases the risk of type 2 diabetes, metabolic syndrome, chronic renal disease, and cardiovascular disease in a person. In current practice, five alternative definitions of prediabetes are utilized, each based on different HbA1c, fasting glucose, and 2-hour glucose cut points. Prediabetes is a common condition that occurs between normal glycemia and diabetes. It is more common in elderly and obese people. The prevalence of prediabetes and diabetes can be influenced by a variety of individual, family, and societal variables. Additionally, as diabetes is the primary contributor to non-communicable diseases (NCD), it is crucial to identify the key temporal variables for diabetes early diagnosis. In turn, effective prediabetes and diabetes awareness, control, and preventive programs may be created by policymakers and public health professionals worldwide. Popular pathogenic pathways in prediabetes include insulin resistance, inflammation, and sensitivity to insulin. HBA1c, OGTT, and FPG are discussed as the diagnostic criteria in order of frequency. The most commonly researched therapies in the realm of prediabetes are metformin, exercise, and physical activity. Physiological markers including BMI, blood pressure, and waist circumference prompted relatively significant concern. Despite declining trends, the study demonstrates that prediabetes and diabetes are widely prevalent. In order to prevent non-communicable illnesses, the research suggests encouraging healthy lifestyles and regular screenings.
Keywords: American diabetes association